Challenges for monetary policy and the enlarged Euroland - Massimiliano Marzo (Free University Berlin, Jean Monnet Centre of Excellence, 2003)
The recent outset of European Monetary Integration with the introduction of a unique currency and a full centralization of monetary policy together with the increasing integration of global capital markets, stimulated a large body of research on monetary policy rules. Since Lucas' critique, the need to find rules which are at the same time simple and accountable has been a first goal for researchers and policy makers. In fact, policy can be effective only if it is credible. Credibility is enhanced thorough the adoption of simple, accountable monetary policy roles.However, the big question is: what kind of rules? This paper tries to address the critical aspects in monetary policy modelling with a special emphasis to Euro-Enlargement.
Keywords: 330; Monetary Policy Modelling